Peran Moderasi Koneksi Politik Pada Pengaruh Karakteristik CEO Terhadap Kinerja Keuangan Perusahaan - Fahrizal Irfan Alfianto; Gugus Irianto; Yeney Widya Prihatiningtias (Jurnal Reviu Akuntansi dan Keuangan, 2024)
Purpose: This study aims to provide empirical evidence of the impact of CEO characteristics (busyness, economic education, ownership) on corporate financial performance with CEO political connections as a moderating variable. Methodology/approach: This research is a quantitative study utilizing secondary data. The sample was taken using purposive sampling method, thereby obtaining data from 352 non-financial companies listed on the IDX during the 2016-2022 time period. The total observations made were 2306. The data was analyzed using multiple regression analysis support by the Stata 14 application. Findings: The regression analysis results indicating CEO economic education has a positive effect on return on asset (ROA). Meanwhile, CEO political connections moderate the positive effect of CEO ownership on corporate financial performance (ROA) and moderate the negative effect of CEO economic education on corporate financial performance (ROA). Practical implications: Companies should consider the characteristics of CEOs in accordance with the company in order to enhance financial performance. In addition, potential CEOs should improve their characteristics to have a positive impact on the corporate financial performance. Originality/value: This research develops a model related to CEO political connections in moderating the influence of CEO characteristics (busyness, economic education, ownership) on company financial performance. Keywords:  CEO Busyness; CEO Education; CEO Ownership; CEO Political Connections; Corporate Financial Performance; Return on Asset (ROA).